Genotypic variation of physiological and morphological traits of seven olive cultivars under sustained and cyclic drought in Mendoza, Argentina - Trentacoste, Eduardo Rafael; Contreras Zanessi, Octavio Ramiro; Beyá-Marshall, Victor; Puertas, Carlos Marcelo (2018)
The effects of two deficit irrigation regimes on the physiological, morphological, vegetative, and reproductive traits of seven olive cultivars were studied in a pot experiment. Specific leaf area (SLA) and SPAD chlorophyll meter reading (SCMR) were measured over the experimental period. Their relationships with physiological traits and with each other were also tested. Three-year-old plants in pots were subjected to control regime (CI replaced daily water use), sustained deficit regime (SDI was applied daily at 35% of CI), and five successive drought cycles of 30 days followed by rewatering (CDI). In all cultivars, SDI decreased stem water potential compared to CI. Under CDI, stem water potential reached the minimum, ∼–8 MPa, but all cultivars recovered to potentials similar to the rewatering period. Stomatal conductance was significantly reduced in both deficit irrigation regimes compared to the control. Rewatering caused a slower recovery of stomatal conductance in ‘Selección Mendoza’, ‘Villalonga’ and ‘Arbequina’ than in the rest of cultivars. Across cultivars, specific leaf area decreased with water deficit, while SCMR increased. Specific leaf area was positively related with stem water potential (R2 = 0.60), stomatal conductance (R2 = 0.44) and trunk growth (R2 = 0.31). In contrast, SCMR values were negatively related with stem water potential (R2 = 0.59), stomatal conductance (R2 = 0.52) and trunk growth (R2 = 0.62). ‘Changlot’, ‘Arauco’ and ‘Nevadillo Blanco’ cultivars maintained lower SLA and higher SCMR under both deficit irrigation regimes and higher stomatal conductance recovery after rewatering. These cultivars also appear to be better adapted to drought prone environments.